Analysis Of Women Strunggle In rejecting Patriarki Culture (Analysis Of Critical Discourse-Sara Mills In The Flm â€œMarlina Si Pembunuh Dalam Empat Babakâ€) - Sumakud, Victoria Philly Juliana (SEMIOTIKA: Jurnal Komunikasi, 2020)
Marlina Si Pembunuh dalam Empat Babak is a story that is reconstructed from the reality that happened to produce a story like the real one in Sumba in 2017. Departing from the social phenomenon of Yappa Marrada namely the abduction of women as a way of forcing men to have women, this film clearly shows how the struggle of women to carry out acts of anarchy for the sake of fighting the Patriarchs. The topic of Women's Struggle draws the attention of researchers to provide information to the public about the existence of gender-biased behavior through this film, and to help the community to be more aware of the presence of women in the community. Researchers used a qualitative approach with the analysis of Sara Mills's critical discourse based on its shape divided into 3 namely the position of the subject, the position of the object, the position of the audience. The results of the research show that the struggle of women in rejecting patriarchal culture is in accordance with the analysis proposed by Sara Mills. The subject showed that the act of women's struggle in rejecting patriarchal culture was represented by the discourse and movements carried out by subjects where women committed acts of anarchy such as poisoning food, cutting their heads, threatening with machetes. The position of the object is described as an actor supporting the movement of the subject, as the party controlled and controlled by the subject.